Al-'Arabiyya (jstor)
Al-?Arabiyya is the annual journal of the American Association of Teachers of Arabic and serves scholars in the United States and abroad. Al-?Arabiyya includes scholarly articles and reviews that advance the study, research, and teaching of Arabic language, linguistics, literature, and pedagogy.
Keywords: Middle East Studies